Argentine industrialization revisited. A stylized review of the vicissitudes of manufacturing production in the long term (1880-2020) - Odisio, Juan (2022)
Synthesis of the evolution of the industrial sector in Argentina from the late 19th century to the present. The article is divided into five major stages that include the deployment of the industry during the agro-export model; the consolidation of a strategy of industrialization by import substitution from the 1930s onwards; the abandonment of industry as a key sector of economic accumulation between 1980 and the 2001 crisis; and the partial recovery of manufacturing production until 2015. Recent years are also reviewed, characterized by a strong retraction of industry as a consequence of the implementation of neoliberal policies and the current international COVID-19 pandemic.